The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/jqs.2724
|View full text |Cite
|
Sign up to set email alerts
|

The Younger Dryas impact hypothesis: a cosmic catastrophe

Abstract: In this paper we review the evidence for the Younger Dryas impact hypothesis (YDIH), which proposes that at ∼12.9k cal a BP North America, South America, Europe and the Middle East were subjected to some sort of extraterrestrial event. This purported event is proposed as a catastrophic process responsible for: terminal Pleistocene environmental changes (onset of YD cooling, continent‐scale wildfires); extinction of late Pleistocene mammals; and demise of the Clovis ‘culture’ in North America, the earliest well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 120 publications
(422 reference statements)
0
34
0
Order By: Relevance
“…Other investigators have pointed out the possibility of a combination of human-caused and climate-related causes of extinction (see discussion in Barnosky et al, 2004). Although all three mechanisms are controversial, the extraterrestrial impact hypothesis has received a significant amount of criticism (e.g., Daulton et al, 2010;Pinter et al, 1998Pinter et al, , 2011Holliday et al, 2014;Meltzer et al, 2014) and is not considered further here. No attempt is made to discuss the pros and cons of the human vs. climate change causes for megafaunal extinction in North America, but some of the findings presented here have relevance to the debate on these two causes for mammoth extinction specifically on the Channel Islands.…”
Section: Implications For Causes Of Mammoth Extinctionmentioning
confidence: 99%
“…Other investigators have pointed out the possibility of a combination of human-caused and climate-related causes of extinction (see discussion in Barnosky et al, 2004). Although all three mechanisms are controversial, the extraterrestrial impact hypothesis has received a significant amount of criticism (e.g., Daulton et al, 2010;Pinter et al, 1998Pinter et al, , 2011Holliday et al, 2014;Meltzer et al, 2014) and is not considered further here. No attempt is made to discuss the pros and cons of the human vs. climate change causes for megafaunal extinction in North America, but some of the findings presented here have relevance to the debate on these two causes for mammoth extinction specifically on the Channel Islands.…”
Section: Implications For Causes Of Mammoth Extinctionmentioning
confidence: 99%
“…Specifically, questions have been raised regarding the nature or replicability of the reported impact proxies, the accuracy of the established chronology, and its purported effects on humans and animals at the YD onset12131415161718. All of these criticisms have been addressed by additional and independent studies replicating the original findings of Firestone et al 371920…”
mentioning
confidence: 99%
“…Indeed, recent evidence from the last few years from three independent research groups has revealed a platinum anomaly that extends at least across North America, Greenland and North-West Europe, coeval with other evidence for a cosmic impact, including impact spherules, magnetic grains and nano diamonds [24][25][26]. Although disputed by several prominent and vocal research groups, their counter-arguments are generally weak to non-existent while evidence from independent research groups continues to accumulate [27][28][29][30][31][32][33][34].…”
Section: A Catastrophe At the Origin Of Civilizationmentioning
confidence: 99%